Hydrogen Evolution in Battery Electric Vehicle Coolants During Accidental Leakage: The Impact of Corrosion Inhibitors and Electrical Conductivity - Luciane Sopchenski; Sander Clerick; Guy Buytaert; Serge Lievens; Theodoros Kalogiannis; Annick Hubin; Herman Terryn (Applied Sciences)
Efficient thermal management is critical to the performance and acceptance of battery electric vehicles (BEVs). In the event of coolant leakage, contact between conventional water–glycol coolants and polarized battery components may induce hydrogen evolution via electrolysis, posing a serious safety hazard. This study investigates the impact of copper corrosion inhibitors and coolant electrical conductivity on hydrogen gas formation through linear sweep voltammetry (LSV) using copper electrodes. Results indicate that commonly used corrosion inhibitors—Tolyltriazole (TTZ), Benzotriazole (BTZ), and Sodium Mercaptobenzothiazole (MBT-Na)—do not significantly reduce hydrogen evolution, even in synergistic combinations. On the other hand, lowering the coolant electrical conductivity markedly decreased hydrogen evolution, with a linear reduction in cathodic current observed in low-conductivity coolants due to the reduced ionic mobility of the electrolyte. Low-conductivity BEV coolant (86 µS/cm) presented a cathodic current density 96% lower than a high-conductivity ICE coolant (2577 µS/cm) at the same overpotential. These findings suggest that optimizing coolant conductivity is a more effective mitigation strategy than relying on corrosion inhibitor formulations.